A new species of the genus Oligodon Fitzinger, 1826 (Squamata: Colubridae) from Langbian Plateau, Vietnam - Nguyen, Sang Ngoc; Le, Manh Van; Vo, Thi-Dieu-Hien; Murphy, Robert W. (Zootaxa, 2022)
We describe a new species of kukri snake from Da Lat City and its vicinity in Lam Dong Province, southern Vietnam on the basis of morphological characters of four specimens, including two males and two females. Oligodon tuani sp. nov. differs from other congeners by a combination of the following characters: large size in adults (TL ≤ 888 mm); 19 dorsal scale rows at midbody; ventrals 173–179 in males and 187–193 in females; subcaudals 58 or 59 in males and 44 or 45 in females; presubocular present; 8 supralabials, fourth and fifth entering orbit; cloacal plate undivided; 10 maxillary teeth, posterior three enlarged; vertebral stripe present; temporal streak present but faint and interrupted; long and deeply forked hemipenes, extending to 25th subcaudal, without spines and papillae; and 13–15+3–4 dorsal blotches.